Fabrication of ILs-Assisted AgTaO3 Nanoparticles for the Water Splitting Reaction: The Effect of ILs on Morphology and Photoactivity - Julia Zwara (Materials, 2020)
The design of an active, stable and efficient photocatalyst that is able to be used for hydrogen production is of great interest nowadays. Therefore, four methods of AgTaO3 perovskite synthesis, such as hydrothermal, solvothermal, sol-gel and solid state reactions, were proposed in this study to identify the one with the highest hydrogen generation efficiency by the water splitting reaction. The comprehensive results clearly show that the solid state reaction (SSR) led to the obtainment of a sample with an almost seven times higher photocatalytic activity than the other methods. Furthermore, four ionic liquids, all possessing nitrogen in the form of organic cations (two imidazoliums with different anions, ammonium and tetrazolium), were used for the first time to prepare composites consisting of AgTaO3 modified with IL and Pt, simultaneously. The effect of the ionic liquids (ILs) and Pt nanoparticles’ presence on the structure, morphology, optical properties, elemental composition and the effectiveness of the hydrogen generation was investigated and discussed. The morphology investigation revealed that the AgTaO3 photocatalysts with the application of [OMIM]-cation based ILs created smaller granules (<500 nm), whereas [TBA] [Cl] and [TPTZ] [Cl] ILs caused the formation of larger particles (up to 2 μm). We found that various ILs used for the synthesis did not improve the photocatalytic activity of the obtained samples in comparison with pristine AgTaO3. It was detected that the compound with the highest ability for hydrogen generation under UV-Vis irradiation was the AgTaO3_0.2% Pt (248.5 μmol∙g−1), having an almost 13 times higher efficiency in comparison with the non-modified pristine sample. It is evidenced that the enhanced photocatalytic activity of modified composites originated mainly from the presence of the platinum particles. The mechanism of photocatalytic H2 production under UV-Vis light irradiation in the presence of an AgTaO3_IL_Pt composite in the water splitting reaction was also proposed.